Meningkatkan Kognitif Anak Usia Dini Melalui Eksperimen Mengenali Beragam Rasa - Sativa, Filsa Era; Wahab, Aulia Dwi Amalina (NANAEKE: Indonesian Journal of Early Childhood Education, 2024)
Science is systematic knowledge obtained through a series of experiments and observations that can be tested further. In early childhood, simple science can foster curiosity, and encourage thoughts and actions such as observing, thinking, and relating concepts or events. Through science learning by conducting simple experiments in early childhood, we can improve aspects of children's development. This research aims to determine the cognitive abilities of young children at TK Negeri Pembina Ampenan through experiments in recognizing various flavors. This research method is classroom action research. The results of the research show that children's cognitive abilities increase from before the action until the action occurs in cycles I and II. Before being given action, it was in the undeveloped category with a value of 38.05%, after taking action in cycle I it developed according to expectations with a percentage of 72.52%, and increased to very well developed in cycle II with a percentage of 90.28%. From the research data, it can be concluded that learning science through simple experiments on recognizing tastes can maximize the cognitive abilities of young children